Contaminants of emerging concern in an endangered population of common eiders (Somateria mollissima) in the Baltic Sea - Ask, Amalie V.; Jaspers, Veerle L.B.; Zhang, Junjie; Asimakopoulos, Alexandros G.; Frøyland, Sunniva H.; Jolkkonen, Juho; Prian, Wasique Z.; Wilson, Nora M.; Sonne, Christian; Hansen, Martin; Öst, Markus; Koivisto, Sanna; et al. (Elsevier Ltd, 2025)
Contaminants of emerging concern (CECs) are ubiquitous in aquatic environments and pose a range of biological effects including endocrine disruption. Yet, knowledge of their occurrence in wildlife including seabirds remains scarce. We investigated the occurrence of selected bisphenols, benzophenones, phthalate metabolites, benzotriazoles, benzothiazoles, parabens, triclosan, and triclocarban in plasma of 18 breeding female common eiders (Somateria mollissima) from an endangered population in the Baltic Sea as most of these CECs have never before been examined in eiders. We sampled blood at the start (T1) and end (T2) of incubation to investigate concentration changes during incubation. As early- and late-breeding eiders tend to differ in how they finance reproduction (local vs stored nutrient reserves), we compared early and late breeders to assess whether CEC concentrations differed by breeding phenology. Of the 58 targeted CECs, 21 were detected in at least one female, with bisphenol A (BPA) and benzophenone-3 (BzP-3) occurring most frequently (T1: 78% and 61%; T2: 61% and 67%, respectively), while mono(2-ethyl-1-hexyl) phthalate (mEHP), BPA, and monoethyl phthalate (mEP) were detected in the highest concentrations (median concentrations 27.1, 12.7, and 11.2 ng/g wet weight, respectively, at T1). No CEC concentrations differed between early and late incubation. Late breeders had significantly higher concentrations of BzP-3, monomethyl phthalate (mMP), and mEP during early incubation (4.55 vs 1.24 ng/g ww, 7.05 vs 3.52, and 11.2 vs < limit of detection (LOD), respectively) and significantly higher concentrations of mMP and mEP during late incubation (6.16 vs